The features of changes in orientations to employment among bachelor’s graduates - A. V. Merenkov; D. G. Sandler; V. S. Shavrin (Obrazovanie i Nauka)
Introduction. Today, there is a whole range of problems related to youth employment. These problems are caused by social, economic, technological, migration reasons, rapid transformation of the labour market structure and all spheres of life of a modern man. The value-motivational attitudes of young people in solving the issue of their employment become different. The aim of the research is to identify the dynamics and qualitative changes in values, which determine the choice of the future workplace by university graduates, as well as the degree of compliance of the claims of young specialists with the requirements imposed by employers.Methodology and research methods. The methodology of the present research is based on the theory of determination of human activity, which reveals the relationship of socio-economic, sociocultural factors, needs, goals, value orientations, personality attitudes in determining the content of the desired job and place of employment. The main research method was a questionnaire survey of bachelor’s students in their final year of studies, who receive technical, economic, humanitarian and pedagogical education in universities of Ekaterinburg – a large Russian industrial and cultural centre. The survey was conducted in 2016 and 2018 according to a single method. At the first stage (2016) the quota sample was 1905 people, at the second stage (2018) – 2420 people. The opinions of the heads of enterprises and organisations of the Ural region on the quality of young specialists’ training, their desire and ability to actively participate in innovation processes were revealed through the method of in-depth interviews.Results and scientific novelty. The results of a comparative study showed the preservation of the graduates’ value orientations to high salaries and opportunities for rapid professional and career growth. At the same time, very significant changes in the direction and content of young people’s orientations to the forthcoming employment were revealed: perceptions of the importance of early search for the profession demanded in labour market and the work in the acquired specialty; values of social status of a specialist with higher education; self-realisation in activities corresponding to personal inclinations and potential. The share of students who do not have clear plans for employment by the time they graduate decreased by half, and the share of technical departments graduates without such plans decreased fourfold. The share of students seeking to raise their social status by receiving a higher education diploma doubled. The number of students focused on obtaining a specialty corresponding to their personal abilities decreased by a quarter. The variation was found in accordance with the specifics of the direction of training of bachelor’s degree students’ determination to continue further studies in master’s degree programmes and their value attitudes for work, including in related specialties. The representatives of enterprises, where students undergo practical training, began to actively help them in finding a job corresponding to their specialty. However, the heads of manufacturing sectors and management staff of various organisations note the inadequacy of ambitions of a large part of applicants for prestigious positions due to the low level of the formation of necessary universal, general professional and professional competencies. According to the employers, there are no noticeable positive changes in the level of readiness of young professionals to actively engage in self-education and continuous professional development, mastering technological innovations.Practical significance. Since the success of graduate employment is an important indicator of university efficiency, the results of the present research can be applied by education management specialists dealing with the issues of the quality of education, career guidance, employment of population and youth policy.